Blockchain-enabled cloud services for secure and transparent data management in SMEs - Ali, Abdifatah Farah; Abdullah, Rusli Haji; Abi Hassan, Abdikarim; Abdullahi, Husein Osman; Mohamed, Mohamud Ahmed (Seventh Sense Research Group, 2024)
This research investigates the key factors affecting the intention of Small and Medium Enterprises (SMEs) to adopt blockchain-based cloud services. The aim is to design sustainable and effective business ecosystems. The study refines the Unified Theory of Acceptance and Use of Technology (UTAUT) model to develop a theoretical framework. This framework evaluates how various factors, such as Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FC), Trust (TR), and Security Concerns (SC), influence the Behavioral Intention (BI) to adopt blockchain-enabled cloud services. To achieve the research objectives, data were collected via an online questionnaire. A total of 273 valid responses from small enterprises in Somalia were collected and analyzed using Structural Equation Modeling (SEM). Empirical evidence indicates that the independent constructs PE, FC, SI, TR, SC, and BI are positively associated. The integration of Security Concerns (SC) and Trust (TR) concepts adds a significant contribution to the existing body of knowledge. The study's outcomes are particularly important for SMEs, offering valuable insights into encouraging technology adoption for sustainable and successful innovation.